ANALISIS KINERJA SUPPLIER KRAFTPAPPER MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS DENGAN PENDEKATAN TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION - Afif, Sofwan; Ramadhania, Sherin; Mislan, Mislan; Rini, Asih Setyo; Gandara, Ganjar Sidik; Hipni, Ahmad (LPPM Universitas Bina Bangsa, 2023)
PT Taco Anugrah Corporindo, which was established in 2017, is the largest producer of High Pressure Laminates (HPL) in Indonesia. PT. Taco Anugrah Corporindo, in carrying out the production process, produces Kraftpapper raw materials that have predetermined standard qualities. The predetermined qualities include quality, price, location and service. To meet the raw material needs of production, you need a raw material supplier that complies with the standards if you choose Suppliers who do not comply with standards can cause poor production quality, many raw materials are rejected, and will cause losses for the company. Therefore, the aim of this research is to determine the performance of Kraftpapper suppliers, so that the production process runs smoothly and the company does not experience losses. AHP is a method that functions to determine the priorities of several suppliers to minimize the occurrence of many production rejects, cost losses and loss time in the company. While TOPSIS is a method used for supplier performance ranking. The result of data processing is that the first priority Kraft paper supplier is PT. IK with the highest assessment result of 0.48872, and the highest rating of Kraft paper supplier performance is PT. IK with a preference value of 0.28634, because it best fits the criteria of the company